Classic imaging features of L-2-hydroxyglutaric aciduria in young adult presenting as seizures associated with fever - Suresh Kumar (Annals of Indian Academy of Neurology, 2020)
L-2 Hydroxyglutaric aciduria is a rare metabolic disorder which is autosomal recessive in inheritance. It is characterised by the increased urinary excretion of L-2 hydroxyglutaric acid and the diagnosis is based on the increased levels of the L-2 hydroxy glutaric acid in the urine, serum & CSF. This is a neurometabolic disorder which is associated with slowly progressive psychomotor delay since childhood. We report a case of an 18 –year old female who presented at the emergency department with seizures, fever and on imaging show classic features.